PENGAMBILAN KEPUTUSAN KEPALA SEKOLAH DALAM RANGKA PEMBERDAYAAN TENAGA PENDIDIK DI SEKOLAH POLISI NEGARA JAMBI - Tita Meitia (Universitas Negeri Jakarta, 2010)
This research performed at Police National Academy in Jambi on year 2009. This research aims to determine; (1) Decision making that were taken by principal in order to empower educators; (2) The level of rationality in decision making by principal in order to empower educators; and (3) Relation between desicion making by principal in order to empower educators at Police National Academy in Jambi. This research included 30 respondent and using Descriptive Methode. Sampling Methode performed by using Stratified random sampling. Data analyzing technique using Descriptive statistic. Decision making that performed by principal at Police National Academy in Jambi in order to empowering educators had improve their motivation, competency, independence, confidence, and team work. Based on finding research, to improve empowerment for educators can be achieved by determining accurate decision that taken by principal.